Ferramentas da Web 2.0 nas bibliotecas universitárias: identificando novas linguagens culturais no SBUFRGS - Colpo, Lenise Di Domenico (2014)
Constant changes are perceived in society by introducing new technologies, especially in the forms of relationship between people. The internet has enabled the expansion of ways of interaction, creating new scenarios and effective means of communication. In the academia, university libraries started using new medias seeking for a larger interaction with their users and also as a facilitator, more comprehensive at the knowledge construction. Named "Web 2.0 tools", they are already part of the daily lives of libraries that aims to approximate with the user increasingly connected to the internet. Authors such as Jesus and Cunha (2012) indicate the dearth of information about the effective use of these tools at the Brazilian libraries. From this context, the present study have as an general objective identify, within the library system of Universidade Federal do Rio Grande do Sul – SBUFRGS, the web 2.0 tools currently used in the provision of services and the dissemination of information and verify if these tools contribute to the library-user relationship. The study used quantitative and qualitative methods: survey data on the Internet, telephone contact, interviews and questionnaire. After the data analyzing, the research followed to the last step which consisted of the preparation of the final product, the creation of aninfographic that seek to illustrate the use of web 2.0 tools in SBUFRGS. The results indicate that only 43% of UFRGS libraries make use of web 2.0 tools, being Facebook as the most used tool, followed by the Blog and Twitter. Concludes that the use of web 2.0 tools contribute in library-user relationship since the use of these tools enhances communication processes resulting in larger proximity relation library user.